Avaliação da atividade antitumoral de complexos organometálicos de rutênio(II) contendo ligantes β-dicetonas - Macêdo, Roberta Rocha (2023)
In this work, the synthesis, characterization and evaluation of the antitumor activity of five monocationic ruthenium(II) organometallic complexes containing β-diketone and pyridine ligands are described. The synthesized complexes presented the general formula [Ru(O-O)(p-cim)(py)]PF6, being (O-O): 4,4,4-trifluoro-1-phenyl-1,3-butanedione (bta) (I), 2 -thenoyltrifluoroacetone (tta) (II), 1-(4-bromophenyl)-4,4,4-trifluoro-1,3- butanedione (tfb) (III), 4,4,4-trifluoro-1-(4-fluorophenyl)butane-1,3-dione (tff) (IV), 1- (4-chlorophenyl)-4,4,4-trifluoro-1,3-butanedione (btc) (V); p-cim: ƞ6-p-cymene and py: pyridine. The complexes were analyzed by usual characterization techniques, such as molar conductivity, elemental analysis, absorption spectroscopy in the infrared and visible ultraviolet region, 1H and 13C{1H} nuclear magnetic resonance spectroscopy, mass spectrometry and X-ray diffraction. In addition, all complexes were studied regarding their stability in the solvents used in the biological tests and it was verified that complexes I and III exhibited a better stability profile in solution. The in vitro antitumor activity assays were performed against histologically distinct tumor cell lines A549, A2780-cis, MCF-7 and MDA-MB-231, and against non-tumor cell lines, MRC-5 and MCF-10A. Through the results obtained, it was possible to infer that the insertion of ligands to the ruthenium precursor promoted an increase in biological activity, since Ru(II)/arene was inactive and the active ligands exhibited lower cytotoxicity than the respective complexes. In this series, all complexes exhibited good cytotoxicity values against the cisplatin-resistant cell lines A2780-cis (IC50 = 5.06 – 10.83 μmol L-1), MCF-7 (IC50 = 10.17 – 34.78 μmol L-1) and MDA -MB-231 (IC50 = 8.25 – 46.14 μmol L-1), emphasizing that compound III was the most active in all tumor cell lines tested (IC50 = 5.07 – 42.47 μmol L-1). For A549, except for II, the other complexes exhibited moderate cytotoxicity. For non-tumorigenic ligeages, the complexes were less toxic than cisplatin for MCF-10A, with emphasis on V, which was inactive. In addition, all complexes were more selective than cisplatin at A2780-cis and for MCF-7, V exhibited selectivity index > 6. All complexes do not interact with DNA by intercalation or covalent binding, and may present reversible interactions and weak. Preliminary tests with BSA demonstrated that complexes I and IV interact with this protein, possibly being associated with the pharmacokinetics of these compounds.